Identity, Belonging and Human Rights - Hadjigeorgiou, Nasia (BRILL, 2019)
This edited volume explores the concepts of identity and belonging, by bringing together both chapters that engage with the two terms on a theoretical and a more practical level. The theoretical chapters, found in Part I of the volume, explore dilemmas and difficult questions that have to do with identity and belonging, while the more practical contributions, found in Part II of the volume, discuss the effects of identity and belonging in our everyday lives. The final chapters, found in Part III, seek to take the discussion on identity and belonging further and explore how these twin concepts relate to and can be seen through the prism of human rights.